دراسة تأثير وعي المستهلك الجزائري بالعلامة التجارية كوندور في بناء صورتها الذهنية - مجاهدي، فاتح; قارطي، حورية; مخلوف، سليمة Makhlouf, Salimah (المركز الجامعي عبد الحفيظ بوالصوف ميلة, 2018)
The aim of this study is to explore the impact of the Algerian consumer Awareness about Condor Brand on its image building using its three dimensions (Cognitive component, Affective component, and the behavioral component). To achieve this goal, the researchers conducted a survey study by distributing a questionnaire on a convenient sample of 700 Algerian respondents in order to test the hypotheses of the study. For this purpose, a number of statistical methods were used: the analysis of variance and linear regression using the SPSS program. The study reached a number of results, where the most important were: * There is a statistical significant impact of Condor Brand Awareness on its image; * There are no significant differences in Condor Brand Awareness from the Algerian consumers' perspective according to their gender, while there are significant differences according to their age, income and educational level; *There are no significant differences in Condor brand image according to gender, age, income and educational level.
هدفت هذه الدراسة إلى معرفة هل يوجد أثر الوعي بالعلامة التجارية كوندور على صورتها الذهنية وكذلك من خلال قياسها بثلاثة أبعاد والمتمثلة في البعد المعرفي، البعد العاطفي والبعد السلوكي، ولتحقيق هذا الهدف قام الباحثين بجمع البيانات اللازمة عن طريق توزيع استبيان على عينة ميسرة من المجتمع الجزائري بلغ حجمها 700 مفردة بغية اختبار فرضيات الدراسة، ولأجل ذلك تم استخدام مجموعة من الأساليب الإحصائية أهمها: تحليل التباين والانحدار الخطي البسيط وذلك بالاستعانة ببرنامج SPSS. وقد توصلت الدراسة إلى مجموعة من النتائج أهمها إلى أنه يوجد أثر ذو دلالة إحصائية لوعي المستهلك الجزائري بالعلامة التجارية كوندور على صورتها الذهنية. توجد اختلافات ذات دلالة إحصائية عند مستوي المعنوية (α≤5%) لوعي المستهلك الجزائري بالعلامة التجارية كوندور باختلاف الجنس، في حين أنه لا توجد اختلافات ذات دلالة إحصائية لوعي المستهلك الجزائري بالعلامة التجارية كوندور باختلاف سنه ودخله ومستواه التعليمي، كما أنه لا توجد اختلافات ذات دلالة إحصائية لإدراك المستهلك الجزائرية لصورة العلامة التجارية كوندور باختلاف جنسه وسنه ودخله ومستواه التعليمي.
Keywords: العلامة التجارية -- الثقافة الاستهلاكية -- علامة كوندور -- الجزائر